Genetic and environmental risk factors for lumbar disc disease in Olympic grappling athletes: a review - Ahmetov, Ildus; Lutomski, Przemysław; Pospieszna, Barbara; Jurasz, Maciej; Wieliński, Dariusz; Doberska, Agnieszka (Akademia Wychowania Fizycznego w Poznaniu)
The authors examine genetic and environmental risk factors for lumbar disc disease in Olympic grappling athletes. The spine is the primary site of injuries in combat sports involving kicking, striking, throwing and joint locking. The execution of such techniques involves multiple repetitions of rapid movements, short maximal muscle contractions, usually with heavy external loads, and frequent training bouts with a partner. This type of training is associated with a significantly increased risk of injuries and overloads of the lumbar spine. The consequences of musculoskeletal overloads are often caused by the insufficient elasticity of the soft tissues.
Keywords: grappling athletes; lumbar spine injuries; genetic environmental factors